Physiological Effects of Single and Double Face Mask Use with Moderate and Vigorous Exercise. Issue 3 (8th July 2022) - LaBotz, Michele; Stroshine, Karli; Dekker, Ellie; Visich, Paul
ABSTRACT: Introduction/Purpose: Exercise is associated with increased exhalation of infectious particles in respiratory disease, and face mask use has become routine during the coronavirus disease 2019 (COVID-19) pandemic to mitigate particle spread. As of February 2022, the U.S. Centers for Disease Control and Prevention (CDC) continues to recommend the use of double masking (i.e., cloth masks worn over a surgical mask) to minimize particle leakage seen with single-mask use. Studies to date have examined the effects of single masks on exercise safety and performance, but the potential added burden during exercise of an additional mask layer has not been evaluated. The purpose of our study was to compare the effects of single and double face mask use during moderate to vigorous exercise. Methods: Fifteen healthy, physically active young adults (mean age = 21.1 ± 0.8 yr; 8 males and 7 females; V˙O2peak = 46.3 ± 11.5 mL·kg −1 ⋅min −1 ) completed the study. This included an initial assessment of V˙O2peak, with subjects returning for three exercise test sessions performed while wearing either a surgical face mask, a cloth face mask, or double masks (i.e., a cloth mask worn over a surgical mask) in a random order. Test sessions consisted of a progressive cycling protocol with 10-min stages at 40%, 60%, and 75% oxygen consumption reserve (VO2 R). Assessments were performed after 5 and 10 min at each exercise intensity and included heart rate, respiratory rate, oxygen saturation, and ratings of perceived exertion and dyspnea. Results: At exercise intensities from 40% to 75% VO2 R, there were no significant differences between cloth masks, surgical masks, and double masking in the measured subjective and physiologic parameters. Conclusions: When compared with surgical and cloth face masks in common use, for the outcomes measured in this study, double masking in accordance with CDC recommendations does not result in significant impairments during moderate to vigorous exercise up to 75% VO2 R in healthy young adults.